Pengaruh Tekanan Kompaksi dan Perekat terhadap Karakteristik Briket Limbah Daun Cengkeh (Department of Mechanical Engineering, Faculty of Engineering, Universitas Negeri Semarang, 2021)
Distillation process leave cloves leaf as waste that was burned as fuel. That means the leaf potential as solid fuel. This study aimed to determine the effect of compacting pressure and binder content on the characteristics of briquettes. Clove leaf waste was dried, then grinded and sieved through mesh 60. Briquetting is carried out at a pressure of 25kgf/cm2 and 50 kgf/cm2 with binder content varied from 10%, 15%, to 20%. Tests were conducted to get proximate composition (ash content, moisture content, volatile matters and fixed carbon), calorific value, density, stability, strength, and rate of combustion. The result showed that the treatments improved mainly the mechanical properties (density, stability, and strength). There was large change of volatile matter and fixed carbon value before and after briquetting but not for three variants of briquette. The calorific value decreased as binder content increased.